2011
DOI: 10.1158/0008-5472.can-10-3151
|View full text |Cite
|
Sign up to set email alerts
|

A Critical Role for GRP78/BiP in the Tumor Microenvironment for Neovascularization during Tumor Growth and Metastasis

Abstract: Glucose-regulated protein 78 (GRP78)/BiP is a multifunctional protein which plays a major role in endoplasmic reticulum (ER) protein processing, protein quality control, maintaining ER homeostasis, and controlling cell signaling and viability. Previously, using a transgene-induced mammary tumor model, we showed that Grp78 heterozygosity impeded cancer growth through suppression of tumor cell proliferation and promotion of apoptosis and the Grp78 þ/À mice exhibited dramatic reduction (70%) in the microvessel de… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
123
0
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 135 publications
(132 citation statements)
references
References 37 publications
7
123
0
2
Order By: Relevance
“…It has been shown that human RA FLSs induce angiogenesis through a VEGF-mediated pathway in immunodeficient mice (del Rey et al, 2009). In parallel with this, we found that Grp78 down-regulation in FLSs resulted in a decrease in the extent of angiogenesis in Matrigel implants microvessel densities (Dong et al, 2011). Furthermore, knockdown of Grp78 using siRNA suppressed human microvascular endothelial cell proliferation and increased apoptosis (Dong et al, 2011).…”
Section: Reduction Of Synoviocyte Proliferation By the Down-regulatiosupporting
confidence: 62%
“…It has been shown that human RA FLSs induce angiogenesis through a VEGF-mediated pathway in immunodeficient mice (del Rey et al, 2009). In parallel with this, we found that Grp78 down-regulation in FLSs resulted in a decrease in the extent of angiogenesis in Matrigel implants microvessel densities (Dong et al, 2011). Furthermore, knockdown of Grp78 using siRNA suppressed human microvascular endothelial cell proliferation and increased apoptosis (Dong et al, 2011).…”
Section: Reduction Of Synoviocyte Proliferation By the Down-regulatiosupporting
confidence: 62%
“…There is increasing evidence indicating that Hspa5 is involved in biogenesis and signal transduction and that it plays important roles in carcinogenesis (54,55). In this study, we investigated Hspa5 function during early embryonic development in Xenopus and showed for the first time that Hspa5 plays an essential role in pronephros formation that is mediated by RA-Lhx1 signaling.…”
Section: Discussionmentioning
confidence: 94%
“…It serves as a central regulator of endoplasmic reticulum (ER) homeostasis due to its multiple functional roles in protein folding and ER calcium binding, and its control of transmembrane ER stress sensor activation (10,11). GRP78 upregulation has been suggested to correlate to metastases (12,13). GAL3, one of the β-galactoside-binding proteins, has been associated with cell proliferation, recognition, adhesion, differentiation, immunomodulation, apoptosis and angiogenesis.…”
Section: A B Resultsmentioning
confidence: 99%